Schwann cells migrate along axons in the absence of GDNF signaling - Heermann, Stephan; Schwab, Markus (BMC neuroscience, 2012)
Background: During development neural crest derived Schwann Cell (SC) precursors migrate to nerve trunks and populate nascent nerves. Axonal ensheathment by SC is a prerequisite for normal nerve function and the integrity of myelinated as well as nonmyelinated axons. To provide adequate support functions, SC colonize entire nerves. One important prerequisite for this is their migration into distal axonal regions. Results: Here, we studied the role of Glial cell line derived neurotrophic factor (GDNF), a TGF-beta related growth factor, for SC migration. To this end we used a superior cervical ganglion (SCG) explant-SC migration assay, GDNF null mutant mouse embryos and a chemical inhibitor for GDNF signaling in combination with time-lapse imaging. We found that GDNF signaling is dispensable for SC migration along murine embryonic sympathetic axons. Furthermore, in vivo analyzes revealed that SC migration along the sciatic nerve is also not dependent on GDNF. Conclusions: In contrast to previous in vitro findings in the sciatic nerve and a SC precursor cell line, our results clearly indicate that GDNF is dispensable for embryonic SC migration. This is demonstrated for the sympathetic nervous system and also for the sciatic nerve in mouse.
Gesehen am 24.10.2018